(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Slums are a common style of housing in many developing metropolitan areas, ranging fromNairobi’s Kibera to Mumbai‟s Dharavi. These slums are overcrowded, unsafe, unhealthy and lack accessto basic services. An estimated 1 billion people will be living in these informal settlements by the year2030 while 35.2 of the urban population in India currently resides in slums (habitatforhumanity, n.d.). Inorder to address this issue, the Maharashtra government established the Slum Rehabilitation Authority(SRA) in December 1995 to facilitate slum redevelopment throughout Mumbai. The SRA has establisheda total of 1481 projects in the urban contexts of Pune Mumbai. This research aims to compare thethermal performance of an urban slum redevelopment project in Pune, India and also study the designoptimization of slum redevelopment. This includes a data collection and experimental simulationapproach to understand the thermal comfort in Slum rehabilitation Projects in Pune. The results of theresearch will help in indicating the performance and design of SRA projects and form a comparativeanalysis of horizontal slums to vertical „slums‟.